(3GdTaG HJYQja Mbhb GdeUWaj (B( (3Udi Gddg Ydjg hSde (B)s - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s ((3YHO GdhgGH Hf eMeO GdYGHO GdbGOQi GdMSfi s)
(3ChdgG (B:s
(3CeG HYO aEP cQQJ Ydi GdSDGd ai eLehY jJVef GdJYQja HbOQ GdeUWai Ydjg hGdSdGe aGYde CcQec Gddg Cfc MedJfi ef Pdc CeQkG EeQkG s
(3BNQgG (B:s
(3bGd GdbGVi gfG GfJgi Gdbhd HfG ajeG MQQfGg hfMeOg JYGdi Ydi eGgOi Edjg ef LeYg hCdge fLR HMeO Gddg cJGH GdTaGA s
(3GdfSNI HgG MhGTs
(3CfWQ GjVG HQbe (B" 115" (3JGQjNs
(3Ydi MGTjJgG JbjjOGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B359 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B630 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B256 s
Keywords: (3GdJGQjNs